Internalizing Gendered Identities: An Analysis of Children’s Conversations about Cartoon Characters - Saman Afzaal (University of Chitral Journal of Linguistics and Literature, 2021)
In today’s digital world, children spend most of their time watching and enjoying cartoons on smart devices. We, therefore, argue that cartoons leave an impact on the identity of children. This research explores how children accumulate gender stereotypes using Bandura’s social learning theory (1977) and identification with media characters’ theory by Cohen (2001). The study investigates how children of 3rd to 5th grade construct identity under the influence of popular cartoon characters. Based on the child-centred methodology, including controlled conversation patterns with children from ten private schools of Islamabad, this study gives children a voice in exploring their gendered identities.  Findings suggest that boys are inclined to save and rescue, show power, desire knighthood, and admire the stout and muscular body of male cartoon characters while girls are fascinated by submissiveness and politeness, beauty, and the ideal physique of female characters. The findings, further, suggest that boys follow the stereotypes; however, in certain instances, girls try to break the traditional stereotypes and express their desire to be independent and powerful. Hence, children in the form of these traits internalize gender stereotypes. This study is significant as it sheds light on how this popular medium inculcates gendered stereotypes in children’s minds shapes their personas and how much they value them.